NASAF - ALLAMA COUNTRY (Journal of Universal Science Research, 2023)
Famous scientists, scholars of hadith and jurists who are famous in the Islamic world created under the pseudonym Nasafi. He was born in the city of Nasaf (Karshi), engaged in science and education in this country, and made the city of Nasaf famous throughout the world.